Isobaric vapor-liquid equilibrium data for the binary systems of dimethyl carbonate with xylene isomers at 93.13 kPa - Yadav, S.S. (Journal of Chemical and Engineering Data, 2017)
Isobaric binary vapor-liquid equilibrium (VLE) data for dimethyl carbonate with xylene isomers (p-xylene, m-xylene, o-xylene, and ethylbenzene) were measured at the local atmospheric pressure of 93.13 kPa by using a dynamic recirculation still. The experimental VLE data were tested and found to be thermodynamically consistent by Herington and Van Ness consistency test. The experimental VLE data were correlated using the Wilson, NRTL, and UNIQUAC activity coefficient models and binary interactions parameters were estimated using a suitable objective function. The absolute mean deviation between the experimental and the model predicted values of vapor phase composition and total pressure was well within acceptable limits. No azeotrope was observed in any of the binary pairs and appeared to be easy for separation using conventional distillation method.
Keywords: Atmospheric Pressure; binary mixture; Distillation; Xylene

Study of the effect of operating parameters on the extractive distillation of isopropyl alcohol–water mixture using dimethyl sulphoxide as an entrainer - Ghuge, Pravin D.; Mali, Nilesh A.; Sirsam, R. S. (Indian Chemical Engineer, 2017)
Abstract: In this paper, the simulation analysis of separation of isopropyl alcohol (IPA)–water via extractive distillation by using dimethyl sulphoxide as an entrainer is presented. The steady-state simulation for this process was done using Aspen Plus simulator. The aim of this work is to study the effect of various operating parameters such as number of stages, molar reflux ratio, binary feed stage number, entrainer feed stage number, temperature of entrainer feed and entrainer to feed molar ratio on the purity and energy consumption. The sensitivity of these parameters serves as a basis to choose the optimum operating conditions to maximize the IPA purity and minimize the energy requirement. In this analysis, among various operating parameters, those which directly affect the IPA purity and the parameters which affect the reboiler duty, for the given separation task, are identified. Simulation results with optimum operating conditions and their economic analysis are also presented.
Keywords: Aspen Plus Simulators; Azeotrope; Computer software; Distillation; Energy requirements; Energy utilization; Extractive distillation; Isopropyl alcohol/water; Isopropyl alcohols; Operating parameters; Optimum operating conditions; Sensitivity analysis; simulation; SimulationSteady-state simulations; Solvents

Study of thermally coupled distillation systems for energy-efficient distillation - Saxena, Neha; Mali, Nilesh; Satpute, Satchidanand (Sadhana-Academy Proceedings in Engineering Sciences, 2017)
Distillation is one of the most widely used separation unit operations in process industries, although it is quite energy intensive. In many cases, the enormous energy requirements for distillation make it economically infeasible to carry out the separation. Thermally coupled distillation system (TCDS) is an advanced distillation method that provides significant energy savings of about 30% as compared with conventional distillation column sequences. The most well-known TCDS sequence, the Petlyuk configuration, has some operational challenges due to bidirectional vapour flow, which makes its implementation difficult in two-column mode. To overcome these limitations, a number of unidirectional vapour flow configurations have been proposed in the literature. The work on simulation analysis for such configurations is limited. In this paper, simulation models for two such configurations are developed, analyzed and compared with the Petlyuk and conventional distillation column sequences for separation of equimolar mixture of benzene-toluene-ethylbenzene.
Keywords: Distillation; energy efficient; Petlyuk; simulation; thermally coupled